2015
DOI: 10.3233/thc-140886
|View full text |Cite
|
Sign up to set email alerts
|

Self-management of hypertension using technology enabled interventions in primary care settings

Abstract: BACKGROUND: Self-management of hypertension by controlling Blood Pressure (BP) through technology-based interventions can effectively reduce the burden of high BP, which affects one out of every three adults in the United States. OBJECTIVE: The primary aim of this study is to explore the role of technology enabled interventions to improve or enhance self-management among individuals with hypertension. METHODS: We conducted a systematic review of the literature published between July 2008 and June 2013 on the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“… Monitoring of blood pressure with feedback was a feature of self-management support in 17 out of 29 reviews, though the monitoring process varied. Home BP monitoring [28,31,35,36,42,46,48,50], was often mediated by telehealth [27,29,32,34,37,41,43,52,53], and in some reviews also included monitoring of medication intake, weight, physical activity and smoking [40,52]. The impact of monitoring on blood pressure control varied, with evidence that monitoring associated with feedback from healthcare professionals (including via telehealth) or as part of a complex intervention to promote medication adherence was more likely to be effective than self-monitoring as an unsupported…”
Section: Effectiveness Of Specific Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“… Monitoring of blood pressure with feedback was a feature of self-management support in 17 out of 29 reviews, though the monitoring process varied. Home BP monitoring [28,31,35,36,42,46,48,50], was often mediated by telehealth [27,29,32,34,37,41,43,52,53], and in some reviews also included monitoring of medication intake, weight, physical activity and smoking [40,52]. The impact of monitoring on blood pressure control varied, with evidence that monitoring associated with feedback from healthcare professionals (including via telehealth) or as part of a complex intervention to promote medication adherence was more likely to be effective than self-monitoring as an unsupported…”
Section: Effectiveness Of Specific Componentsmentioning
confidence: 99%
“…Regular clinical review  Symptoms are commonly reported and should be acknowledged 21,23,26 9 reviews included regular clinical reviews 37,39,40,42,43,46,49,52,53 A5. Monitoring of condition with feedback  Interventions like self-monitoring of BP (HBPM) can foster therapeutic alliance 22 and promote a more internal locus of control 18 reviews included HBPM [27][28][29]31,32,[34][35][36][37][41][42][43]46,48,50,52,53,56 with evidence that feedback (e.g. via telehealth) improved effectiveness 27,29,32,34,37,41,43,52,53,56 A6.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
See 2 more Smart Citations
“…73 The inclusion of technology-based or mobile health (mHealth) interventions 74, 75 should be considered to test whether they can enhance culturally-appropriate community-based programs. This can include telephone-delivered hypertension management programs 76, 77 in conjunction with HBPM, or ABPM and/or mobile phone text messaging to support medication adherence. 78, 79 Smartphone technology can also be used to facilitate data collection, including ecological momentary assessments among JHS participants between study visits and deliver or re-emphasize healthcare education 80 and lifestyle interventions.…”
Section: Treatment and Control Issuesmentioning
confidence: 99%